Exploring the relationship between appendicular skeletal muscle index and urge urinary incontinence risk in adult women: a cross-sectional analysis of the National Health and Nutrition Examination Survey - Jinyu Liu; Kangqiang Weng; Guowei Lin; Huaiding Tang; Jianbing Xie; Lixian Li (Frontiers in Nutrition)
ObjectiveThis study aimed to investigate the relationship between the appendicular skeletal muscle index (ASMI) and Urge urinary incontinence (UUI) in a large cohort of adult women.MethodsThis study utilized data from the National Health and Nutrition Examination Survey during the periods of 2001–2006 and 2011–2018. ASMI was identified as the exposure factor. UUI was the outcome variable. We first compared the baseline characteristics of individuals with and without UUI. The effect of ASMI on UUI was assessed using weighted multivariate logistic regression models. Additionally, the relationship between the two was illustrated using restricted cubic splines.ResultsA total of 19,009 women aged 20 and above participated in this study, with 5,960 diagnosed with UUI and 13,049 not affected. The results of the adjusted multivariate logistic regression analysis showed a significant inverse relationship between ASMI and the probability of UUI. Specifically, with every one-unit rise in ASMI, the likelihood of UUI diminished by 69% in the fully adjusted model (OR = 0.31; 95% CI: 0.12–0.82; p = 0.02). Furthermore, participants falling within the highest ASMI quartile showed a 28% reduction in UUI risk relative to those in the lowest quartile (OR = 0.72; 95% CI: 0.55–0.94; p = 0.02). A restricted cubic spline analysis demonstrated a nonlinear relationship between ASMI and UUI (p for nonlinearity = 0.02). Subgroup analyses suggested that various demographic and health factors did not significantly alter this association.ConclusionThe ASMI was significantly negatively correlated with the risk of UUI, suggesting that an increase in ASMI may have been associated with a lower risk of UUI.